(untitled) (Pedagogy of Higher and Secondary Education, 2003)
The development of imaginative way of thinking in educational process is an essential to-days demand because the future labor activity of school — leaves in the up-to-date conditions of production computerization demands operations connected not with the real objects themselves, but with their simulators, such as three-dimension models, control-boards, etc.